2008
DOI: 10.1021/jf800651z
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Fungicidal Activities of Novel Bis(trifluoromethyl)phenyl-Based Strobilurins

Abstract: Strobilurins have become one of the most important classes of agricultural fungicides. To search for novel strobilurin compounds with unique biological activities, novel bis(trifluoromethyl)phenyl-based strobilurin analogues were synthesized by the reaction of 1-bis(trifluoromethyl)phenyl based methanone oxime with corresponding strobilurin pharmacophores in the presence of bases such as potassium hydroxide, potassium carbonate, or sodium hydride. ( E)-Methyl 2-(2-(((( Z)(1-(3,5-bis(trifluoromethyl) phenyl)-1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 8 publications
0
21
0
Order By: Relevance
“…As shown in Table 3, HNPC‐A3066 has been found to be an effective acaricide for control of various acarids on cotton and fruit trees, without observable phytotoxicity in practical treatments ranging from 60 to 120 g ha −1 . Greenhouse and field trials also showed a good efficacy for the control of phytopathogenic fungal species, details of which will be published elsewhere 15…”
Section: Resultsmentioning
confidence: 96%
“…As shown in Table 3, HNPC‐A3066 has been found to be an effective acaricide for control of various acarids on cotton and fruit trees, without observable phytotoxicity in practical treatments ranging from 60 to 120 g ha −1 . Greenhouse and field trials also showed a good efficacy for the control of phytopathogenic fungal species, details of which will be published elsewhere 15…”
Section: Resultsmentioning
confidence: 96%
“…Initial attempts to introduce the spacer arm at the required positions directly on PY failed, so haptens had to be finally prepared by total synthesis starting 45 from ready available materials. We used an adaptation of the strategy previously reported for the preparation of PY 8 and related compounds, 9 which involved, for such cases, the alkylation of a 1-aryl-1H-pyrazol-3-ol with a methyl 2-(bromomethyl)-phenyl(methoxy)carbamate as the key 50 synthetic step for the elaboration of the characteristic PY framework.…”
Section: Chemistrymentioning
confidence: 99%
“…Isoxazoline 23 was prepared by a cycloaddition of the nitrile-oxide derived from oxime 22 17 with N-(4-chlorophenyl)but-3-enamide18 (Scheme 5). Triazoles 29 and 31 were prepared from anilines 28 and 30 , respectively, by azidation and copper-catalyzed Click cyclization with alkyne amides 25 and 27 (Scheme 6).…”
mentioning
confidence: 99%